Combination Therapy with GABA and MgSO4 Improves Insulin Sensitivity in Type 2 Diabetic Rat. (15th February 2022) - Sohrabipour, Shahla; Sharifi, Mohammad Reza; Sharifi, Mohammadreza; Talebi, Ardeshir; Soltani, Nepton
Abstract : Background. Gamma-aminobutyric acid (GABA) and magnesium sulfate (MgSO4 ) play a crucial role in glycemic control. Therefore, we studied the effect of combination therapy with GABA and MgSO4 to improve insulin sensitivity in diabetes induced by streptozotocin as well as high-fat diet in a diabetic rat model. Design and Methods . Forty randomly selected rats were assigned to four groups: nondiabetic control group was fed the normal diet, insulin-resistant diabetic rat model was induced by streptozotocin and high-fat diet, GABA + MgSO4 group received GABA and MgSO4, and insulin group was treated with insulin. Body weight, abdominal fat, blood glucose, serum insulin, and glucagon concentration were measured. The glucose clamp technique, glucose tolerance test, and insulin tolerance test were performed to study insulin sensitivity. Also, the expressions of glucose 6 phosphatase, glucagon receptor, and phosphoenolpyruvate carboxykinase genes in liver were assessed for the gluconeogenesis pathway. Protein translocation and glucose transporter 4 ( Glut4 ) genes expression in muscle were also assessed. Results . Combination of GABA + MgSO4 or insulin therapy enhanced insulin level, glycemic control, glucose and insulin tolerance test, some enzymes expression in the gluconeogenesis pathway, body fat, body weight, and glucagon receptor in diabetic rats. Moreover, an increase was observed in protein and gene expression of Glut4 . Insulin sensitivity in combination therapy was more than the insulin group. Conclusions . GABA and MgSO4 enhanced insulin sensitivity via increasing Glut4 and reducing the gluconeogenesis enzyme and glucagon receptor gene expressions.